Association of breast cancer risk and the mTOR pathway in women of African ancestry in 'The Root' Consortium. (5th June 2017) - Wang, Shengfeng; Huo, Dezheng; Ogundiran, Temidayo O; Ojengbede, Oladosu; Zheng, Wei; Nathanson, Katherine L; Nemesure, Barbara; Ambs, Stefan; Olopade, Olufunmilayo I; Zheng, Yonglan
Summary: We found a significant association between the entire mTOR pathway and breast cancer risk, particularly with overall and ER− breast cancer risk in women of African ancestry, driven primarily by two different genes, PRKAG3 and RPS6KA3, respectively. Abstract: Functional studies have elucidated the role of the mammalian target of rapamycin (mTOR) pathway in breast carcinogenesis, but to date, there is a paucity of data on its contribution to breast cancer risk in women of African ancestry. We examined 47628 SNPs in 61 mTOR pathway genes in the genome wide association study of breast cancer in the African Diaspora study (The Root consortium), which included 3686 participants (1657 cases). Pathway- and gene-level analyses were conducted using the adaptive rank truncated product (ARTP) test for 10994 SNPs that were not highly correlated ( r 2 < 0.8). Odds ratio (OR) and 95% confidence interval (CI) were estimated with logistic regression for each single-nucleotide polymorphism. The mTOR pathway was significantly associated with overall and estrogen receptor-negative (ER−) breast cancer risk ( P = 0.003 and 0.03, respectively). PRKAG3 ( P adj = 0.0018) and RPS6KA3 ( P adj = 0.061) were the leading genes for the associations with overall breast cancer risk and ER− breast cancer risk, respectively. rs190843378 in PRKAG3 was statistically significant after gene-level adjustment for multiple comparisons (OR = 0.50 for each T allele, 95% CI = 0.38–0.66, P adj = 3.6E−05), with a statistical power of 0.914. These results provide new insights on the biological relevance of the mTOR pathway in breast cancer progression and underscore the need for more genetic epidemiology studies of breast cancer in the African Diaspora.